Developing players` tactical knowledge using combined constraints-led and step-game approaches—a longitudinal action-research study - Ramos, A.; Coutinho, P.; Ribeiro, J.; Fernandes, O.; Davids, K.; Mesquita, I. (Research Quarterly for Exercise and Sport, 2021)
Purpose: Using an action-research design, this study examined the impact of combining concepts from two contemporary pedagogical approaches, the Constraints-led Approach (CLA) and Step-Game Approach (SGA), on the development of youth volleyballers` tactical knowledge, as expressed in performance, throughout a full competitive season.